Data base and erosion risk map creation at Trichonida lake using fuzzy sets and G.I.S. - ΣΑΜΠΩ Β.; ΓΚΟΥΡΝΕΛΟΣ Θ.; ΕΥΕΛΠΙΔΟΥ Ν.; ΒΑΣΙΛΟΠΟΥΛΟΣ Α. (Bulletin of the Geological Society of Greece, 2001)
Trichonida lake has an area of 96,17Km2 and is situated at Etoloakarnania prefecture. In this study a data base has been developed, on geological, geomorphological and environmental data, concerning the wider zone around Trichonida lake. Different thematic maps have been created, using as input variables, the GIS database fields and the statistical analysis output from the MathLab software. Using MathLab software, the primary data has been transformed into fuzzy data sets and for each drainage basin an erodibility value was calculated. The final thematic map, present the erodibility values of each drainage basin. Such geographical GIS databases may be used in local or regional level for the study of erodibility problems, the development of thematic maps and moreover to decision support systems.